Oscillators Near Hopf Bifurcation - Samajova, Helena; Li, Tongxing (Communications - Scientific letters of the University of Zilina, 2015)
In this paper the differential transformation method (DTM) is employed to solve a system of linear differential equations derived for energy optimal control theory and nonlinear differential equations and their systems for oscillators near Hopf bifurcation. They are given by differential equations in a complex plane. Different types of forced terms are considered. The approximate solutions are given in the form of series with required accuracy. Some numerical examples are provided.